The Effect of Science Projects Through The Edmodo Platform to Enhance Critical Thinking And Students' Science Motivation: A Mixed-Method Study - Fatimah, S.; Chamdani, M.; Trisnawati, O. R.; Mahmudah, U. (Universitas Negeri Yogyakarta, 2024)
Covid-19 has changed every aspect of life including the world of education. The changing of the learning system presents challenges for education stakeholders. Face-to-face learning has turned into online-based learning. The study aimed to analyze the effect of project-based learning through Edmodo to enhance students' critical thinking skills and science motivation. It was a mixed-method study using an explanatory sequential design. The study was conducted for 1 semester on the second-semester students involving 140 students and divided into 4 classes. One of the classes became the control class. The purposive sampling technique was used in the sampling stage. The instruments were tests, questionnaires, interviews, observations, and documentation. The data analysis techniques were N-Gain and MANOVA strengthened by qualitative data through the stages of data collection, data reduction, data display, and conclusions. The results indicate an effect of project-based learning through Edmodo on the student's critical thinking skills and science motivation. The value of the increase in critical thinking skills and science motivation in the experimental class is better than in the control class by reviewing the N-Gain value.